Comparative Study of Multi-Delay Pseudo-Continuous Arterial Spin Labeling Perfusion MRI and CT Perfusion in Ischemic Stroke Disease - Xu, Xi; Tan, Zefeng; Fan, Meng; Ma, Mengjie; Fang, Weimin; Liang, Jianye; Xiao, Zeyu; Shi, Changzheng; Luo, Liangping (Frontiers in Neuroinformatics, 2021)
With the ageing population, stroke has gradually become the leading cause of death and disability among adults. It is necessary to verify whether multi-delay pseudo-continuous arterial spin labelling (pCASL) MRI can be used as a standard neuroimaging protocol in the patients with ischemic stroke. We aimed to investigate the clinical utility of multi-delay pCASL for evaluating cerebral perfusion in ischemic stroke disease. Twenty-one ischemic stroke patients [18 men and 3 women; median age, 62 years (age range, 37-84 years)] were enrolled in this study. All patients underwent examinations, including the multi-delay pCASL protocol (using 6 PLDs between 1000-3500 ms) and computed tomography perfusion (CTP). The cerebral blood flow (CBF) and arterial transit time (ATT) maps were obtained by the multi-delay pCASL protocol, while CBF and mean transit time (MTT) maps were derived by CTP measurements. Based on the voxel level analysis, Pearson correlation coefficients were used to estimate the associations between the two modalities in the gray matter, white matter, and whole brain of each subject. Moderate to high positive associations between ASL-CBF and CTP-CBF were acquired by voxel level wise analysis in the gray matter, white matter, and whole brain of the enrolled patients (all P<0.005), and the average Pearson correlation coefficients were 0.647, 0.585 and 0.646, respectively. Highly significant positive correlations between ASL-ATT and CTP-MTT were obtained by voxel-level-wise associations in the gray matter, white matter, and whole brain (all P<0.005), and the average Pearson correlation coefficients were 0.787, 0.706 and 0.799, respectively. In addition, significant associations between ASL and CT perfusion were obtained in gray and white matter and whole brain, according to the subgroup analyses of patients’ age and disease stage. There is a correlation between perfusion parameters from multi-delay pCASL and CT perfusion imaging in patients with ischemic stroke. Multi-delay pCASL is radiation-free and non-invasive, and could be an alternative method to CT scans for assessing perfusion in ischemic stroke disease.